Prevalence and Risk Factors of Work Related Musculoskeletal Disorders among occupational versus physical therapists in Saudi Arabia: Musculoskeletal Disorders among occupational versus physical therapists - Abd El-Kader, Shehab Mahmoud; Qawagzah, Subhi Mustafa; Alsulimani, Ibrahim; Alsaiari, Osama; Alsail, Khaled (J Med Rehab Sci, 2024)
Background: Work-Related Musculoskeletal Disorders (WMSD) is considered one of the worldwide major problems across the health care system and It affects the productivity, quality of work and the employee’s daily life activities. Objective: This study was designed to find out the prevalence and possible associated factors of WMSDs among occupational therapists versus physical therapists in Saudi Arabia. Material and Methods: A cross-sectional study in which an online questionnaire was circulated through social media applications to target occupational and physical therapist in Saudi Arabia only 363 subjects completed the questionnaire. The questionnaire consisted of three sections (1) an introduction to explain the study goals; (2) questions about demographic information such as gender, years of experience, the highest educational degree completed, work setting, and specialty; (3) questions about the anatomic distribution of musculoskeletal injuries, potential risk factors, and coping responses to injuries. Results: There was a high prevalence of WRMSDs among 363 occupational and physical therapists who completed the survey. The most affected regions were knees (92.6%) followed by lower back area (72.7%), neck (54.5%), upper back area (41%) and shoulder (38%).The most commonly associated job risk factor for WRMSDs is working in awkward positions such as bending knees of flexing back (71.3%) followed by dealing with heavy patients (60.6%). In addition, there were significant differences between occupational and physical therapists regarding prevalence and risk factors of work related musculoskeletal disorders (P<0.05). Conclusion: The WRMSDs are common among occupational and physical therapists in Saudi Arabia. The most common risk factors were working in awkward positions such as bending knees of flexing back followed by dealing with heavy patients. There is a need to develop ergonomics training programs and effective interventions to overcome WRMSDs and improve working environment among occupational and physical therapist.